2000
DOI: 10.1097/00007632-200003010-00006
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Porous Ceramic as a Bone Graft Substitute in the Surgical Management of Scoliosis

Abstract: These results justify and favor the use of calcium phosphate ceramics as bone graft substitutes for instrumented posterior spinal fusion in teenagers and young adults. Potentially hazardous harvesting of pelvic bone is no longer necessary for such operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
0
8

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(69 citation statements)
references
References 24 publications
1
60
0
8
Order By: Relevance
“…Delecrin et al [19] in a clinical study compared two groups of adolescent and young adult patients who were operated posteriorly for idiopathic scoliosis autogenous and received CD instrumentation supplemented with either autologous IBG or porous biphasic calcium phosphate ceramic blocks, comprising HA and tricalcium phosphate mixed with local bone chips. These authors showed that the patients who received ceramics had lower blood loss were free from postoperative local complications, while radiographically there was demonstrated successful incorporation of the ceramic blocks within 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Delecrin et al [19] in a clinical study compared two groups of adolescent and young adult patients who were operated posteriorly for idiopathic scoliosis autogenous and received CD instrumentation supplemented with either autologous IBG or porous biphasic calcium phosphate ceramic blocks, comprising HA and tricalcium phosphate mixed with local bone chips. These authors showed that the patients who received ceramics had lower blood loss were free from postoperative local complications, while radiographically there was demonstrated successful incorporation of the ceramic blocks within 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…In applying their results of animal studies to clinical practice, Delecrin et al, in a prospective randomized study, assessed the clinical and radiologic performances of a synthetic ceramic as a bone graft substitute in scoliosis surgery [10]. Fifty-eight patients with idiopathic scoliosis underwent posterior correction and arthrodesis by posterior spinal fusion using autogenous iliac bone grafts alone or in combination with porous biphasic calcium phosphate ceramic blocks comprised of HA/TCP.…”
Section: Human Clinical Studiesmentioning
confidence: 99%
“…A synthetic porous ceramic as a bone graft substitute in the surgical management of Delecrin et al (23) scoliosis: a prospective, randomized study.…”
mentioning
confidence: 99%
“…envolvendo BMP-2 (5)(6)9,15,17,(20)(21) , três utilizando BMP-7 (10)(11)19) , sete envolvendo biocerâmicas, como hidroxiapatita, fosfato tricálcio e sulfato de cálcio (12)(13)(14)16,18,(22)(23) . O substituto ósseo mostrou-se equivalente ao enxerto autólogo em 19 estudos (4)(5)(6)(7)(8)(9)(10)(11)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) e inferior em três (12,(24)(25) .…”
unclassified
See 1 more Smart Citation